A decision-support framework for Lean, Agile and Green practices in product life cycle stages. Issue 10 (27th July 2021) - Udokporo, Chinonso; Anosike, Anthony; Lim, Ming
Abstract: Improving operations performance is often achieved through the application of practices such as Lean, Agility and Green (LAG) practices. However, the wide choice of LAG practices available to address customer requirements can be challenging for those with limited knowledge of LAG practices and their efficacy. Therefore, this research provides a framework for selecting appropriate LAG practices that considers product life cycle (PLC) stages for more effective application of practices. The framework was developed following thorough literature review to capture LAG practices. These form the basis for decision making tools incorporated within the framework including an analytic hierarchy process (AHP), statistical inference and regression analysis, ensuring a systematic approach to the analysis and decision support. The framework was verified and validated through a Delphi study and case study respectively. This research makes a contribution to the body of knowledge by providing a framework which could serve as a guide for businesses in the fast moving consumer goods (FMCG) industry to systematically integrate and adopt LAG to better manage their processes and meet customer requirements.